PENGARUH BATUAN DAN SERESAH PADA PERMUKAAN TANAH TERHADAP PENDUGAAN LONGSOR HASIL SIMULASI - Oktaviani Putri Lestari; Sri Rahayu Utami; Christanti Agustina (Departemen Tanah, Fakultas Pertanian, Universitas Brawijaya, 2022)
Landslide is a natural disaster that often occurs in Indonesia. The total of landslides from 2003 to 2018 is 363, which were caused by controlling factors and triggering factors or restraining factors. The relation between two factors (litter and rock) that cause landslide is still rarely researched. This research was carried out from September 2020 to March 2021, in Agro Techno Park Cangar and Jatimulyo Experimental Station. A simulation used an acrylic box (100 cm x 50 cm x 75 cm), with soil 20 cm thick on an aluminium plate adjusted at a slope of 50°. Rainfall intensity was set at 70 mm hour-1, using an Adjustable Water Gun (as a rainfall simulator) with a current of 2.6 amperes rotation sprayer A. There were eight combination treatments consisting of three factors. The variables measured were landslide duration and volume. Data obtained were then analyzed using an unpaired t-test. Apparently, the faster the landslide occurs, the larger the avalanche volume. Among the three factors observed (soil texture, litter and rocks at the surface), surface litter was the most determining factor for landslide duration and volume. Landslide duration and volume were far different between the two soil textural classes when there was no litter at the soil surface. In contrast, if there was 3 cm litter, landslide duration and volume were quite similar between the two soil textural classes. To a small extent, the occurrence of the rocks at the soil surface may fasten and increase landslide volume.